2023
DOI: 10.1021/acsomega.2c08079
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Deep Eutectic Solvents to Provoke Solubility and Bioavailability of Naringin: Implications of a Computational Approach

Abstract: Recently, the applications of deep eutectic solvents (DESs) as green and sustainable solvents for the solubilization of functional foods and phytophenols have dramatically risen concerning global issues on the utilization of organic solvents. Nevertheless, developing a suitable DES system for phytocomponents to enhance its solubility and bioavailability is complex and requires a sound experimental setup. Herein, we have attempted to develop DES encompassing the choline chloride (ChCl) along with oxalic acid (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Then, after oral administration of NG for 8 h, the concentration of naringenin obtained from naringin in the body reaches a maximum of approximately 2600 ng/mL [ 15 ]. After oral administration of 50 mg/kg NG for 6 h, the plasma concentration of NG in rats reaches the maximum of only 500 ng/mL [ 16 ]. This limitation has been attributed to NG’s low solubility and permeability, which curtails its applicability in the pharmaceutical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Then, after oral administration of NG for 8 h, the concentration of naringenin obtained from naringin in the body reaches a maximum of approximately 2600 ng/mL [ 15 ]. After oral administration of 50 mg/kg NG for 6 h, the plasma concentration of NG in rats reaches the maximum of only 500 ng/mL [ 16 ]. This limitation has been attributed to NG’s low solubility and permeability, which curtails its applicability in the pharmaceutical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Chen et al [ 12 ] suggested that oral administration of a salvianolic acid–DES formulation with a choline chloride–glycerol (1:2) DES resulted in enhanced Cmax and reduced Tmax compared to the corresponding aqueous suspension. Recently, Dangre et al [ 13 ] showed that two-fold enhancement of the relative oral bioavailability of naringenin was achieved with a narigenin–DES formulation with choline chloride–glycerol (1:3) compared to aqueous suspension. However, more investigations are needed to completely understand the oral absorption-enabling potential of DES and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%